An 8-year-old Biological Female Who Identifies Herself as a Boy: Perspectives in Primary Care and from a Parent. Issue 1 (February 2017) - Kern, Leah; Edmonds, Penn; Perrin, Ellen C.; Stein, Martin T.
Abstract : CASE: An 8-year 8-month-old biological female who self-identifies as a boy, Ricardo is brought by his mother for a well-child check to his new pediatrician. Ricardo and his mother report that he is doing well, but have concerns about the upcoming changes associated with puberty. Ricardo states that he is particularly afraid of developing breasts. His mother asks about obtaining a referral to a specialist who can provide "hormone therapy" to delay puberty. Ricardo was adopted from Costa Rica at the age of 2 as a healthy girl named "Angela." From the age of 3, he displayed clear preference for male gender–associated clothes, toys, and games. At age 5, his mother sought care for hyperactivity and sleep problems. He was diagnosed with attention-deficit hyperactivity disorder and sleep onset disorder at age 6, and his symptoms have been well controlled with Adderall and melatonin. Ricardo lives with his parents who are accepting and supportive of his gender preference. He sees a therapist who has experience with gender dysphoria. For the past years, he has attended school as male, with the confidential support of administrators at his elementary school.